Пассивные континентальные структуры и их углеводороды - Дерябин, Н.И. (Пассивные континентальные структуры и их углеводороды / Н.И. Дерябин // Доп. НАН України. — 2008. — № 5. — С.117-120. — Бібліогр.: 4 назв. — рос., 2008)
The conditions, under which hydrocarbon structures (рassive continental rifts, deterioorogenic depressions, and marginal troughs) are formed, are considered. The conclusion is made about their production potential on the presence of hydrocarbon accumulations.